2001
DOI: 10.1159/000053951
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diclofenac Sodium Administration during Pregnancy in the Postnatal Period

Abstract: Objective: The present study aimed to investigate the possible postnatal effects on the liver, kidney and testicular tissues of the offspring of rats given diclofenac sodium (DS) during pregnancy. Methods: At the beginning of the experiment, 80 rats (20 males and 60 females) were raised together for mating purposes. At the end, 50 pregnant rats were obtained and used as the experimental subjects. All pregnant rats were divided into 2 groups, each with 25 rats. The rats of the control group received physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
3
7
0
Order By: Relevance
“…It will affect the mechanism of oxidative stress and causes damage to cells and cellular compounds (Khan & Ahmed, 2009). The activity of diclofenac results in the elevation of ROS, which ultimately results in peroxidative damage in the kidney (Della Torre et al, 2016;Gökçimen et al, 2001). Studies on diclofenac-induced rats have been observed to exhibit anemia.…”
Section: Clinical Features Of Diclofenac-induced Toxicitymentioning
confidence: 99%
“…It will affect the mechanism of oxidative stress and causes damage to cells and cellular compounds (Khan & Ahmed, 2009). The activity of diclofenac results in the elevation of ROS, which ultimately results in peroxidative damage in the kidney (Della Torre et al, 2016;Gökçimen et al, 2001). Studies on diclofenac-induced rats have been observed to exhibit anemia.…”
Section: Clinical Features Of Diclofenac-induced Toxicitymentioning
confidence: 99%
“…Recently, there is evidence of good placental transfer of DS in human; the concentration of DS in fetal tissue was high and similar to that of maternal serum 5 . DS has also been shown to have teratogenic and postnatal effects in rat models 6,7 . Animal studies had proven the development of tricuspid regurgitation, atrial right to left shunting, and right ventricular hypertrophy as the result of sustained right ventricular overload after fetal ductus ligation 8−10 .…”
Section: Discussionmentioning
confidence: 99%
“…5 DS has also been shown to have teratogenic and postnatal effects in rat models. 6,7 Animal studies had proven the development of tricuspid regurgitation, atrial right to left shunting, and right ventricular hypertrophy as the result of sustained right ventricular overload after fetal ductus ligation. [8][9][10] In addition, fetal pulmonary hypertension due to intrauterine closure of the ductus also gives rise to media thickening of pulmonary arterioles, which impede the postnatal fall in pulmonary vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicates that a reduction in cardiac ventricular wall volume and the histological changes observed in the cardiac ventricular muscle are not directly due to the contraction of DA. They may be the combined effects of DS and its metabolites and the side effects of DS-deregulated umbilical cord blood circulation (36). Two different examinations were made of the 20-weekold rats, which were exposed to the same DS doses during the same period and days of uterine life.…”
Section: A B Cmentioning
confidence: 99%